Association of Doppler parameters with placental signs of underperfusion in late‐onset small‐for‐gestational‐age pregnancies. (7th August 2014) - Parra‐Saavedra, M.; Crovetto, F.; Triunfo, S.; Savchev, S.; Peguero, A.; Nadal, A.; Gratacós, E.; Figueras, F.
ABSTRACT Objective To elucidate the association between Doppler parameters and histological signs of placental underperfusion in late‐onset small‐for‐gestational‐age (SGA) babies. Methods Umbilical, fetal middle cerebral and uterine artery pulsatility indices and umbilical vein blood flow (UVBF), which had been recorded within 7 days prior to delivery, were analyzed from a cohort of SGA singleton pregnancies delivered after 34 weeks' gestation and confirmed as having a birth weight < 10th percentile by local standards. In each case, the placenta was histologically evaluated for signs of placental underperfusion using a hierarchical and standardized classification system. The independent association of the Doppler parameters with placental underperfusion was evaluated using logistic regression and decision tree analysis. Results In 51 cases (53.7%), there were 61 placental histological findings indicative of placental underperfusion. These cases had a significantly higher incidence of Cesarean section for non‐reassuring fetal status (52.1% vs 11.9%; P < 0.001) and neonatal metabolic acidosis at birth (21.6% vs 0%; P = 0.001). Significant and independent contributions to the presence of placental underperfusion lesions were provided by increased mean UtA pulsatility index (PI) (P = 0.018; odds ratio (OR) 2 (95% CI, 1.1–3.7)) and decreased UVBF normalized to estimated fetal weight (P = 0.027; OR 0.97 (95% CI, 0.95–0.99)). The combination of both parameters revealed three groups with differing risks for placental underperfusion: normalized UVBF > 82 mL/min/kg (risk 31.3%), normalized UVBF ≤ 82 mL/min/kg and mean UtA‐PI ≤ 95th percentile (risk 65.5%), and normalized UVBF ≤ 82 mL/min/kg and UtA‐PI > 95th percentile (risk 94.4%). Conclusions In late‐onset SGA pregnancies, uterine Doppler and UVBF are surrogates for placental underperfusion. These findings facilitate phenotypic profiling of cases of fetal growth restriction among the general population of late‐onset SGA babies. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd